2012
DOI: 10.1111/j.1743-6109.2011.02366.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Incontinence Surgery on Sexual Function: A Systematic Review and Meta-Analysis

Abstract: Introduction Urinary incontinence has an adverse impact on sexual function. The reports on sexual function following the treatment of urinary incontinence are confusing. Aim To investigate the impact of surgery for stress incontinence on coital incontinence and overall sexual function. Methods Cochrane Incontinence Group Specialized Register of Controlled Tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
2
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(86 citation statements)
references
References 37 publications
4
74
2
2
Order By: Relevance
“…The authors suggested that TOT had positive effect on female sexual functions by reducing urinary leakage and pain during or after sexual activity. In a systematic review evaluating 21 articles assess- ing sexual functions and/or coital incontinence following continence surgery in the absence of prolapse in 1,271 women, there was significant reduction in coital incontinence postoperatively [2]. Similar results were observed in other studies [4,8,18,30].…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…The authors suggested that TOT had positive effect on female sexual functions by reducing urinary leakage and pain during or after sexual activity. In a systematic review evaluating 21 articles assess- ing sexual functions and/or coital incontinence following continence surgery in the absence of prolapse in 1,271 women, there was significant reduction in coital incontinence postoperatively [2]. Similar results were observed in other studies [4,8,18,30].…”
Section: Discussionsupporting
confidence: 73%
“…The mean age of menopause was 46.7 ± 5.2 (31-53); the mean number of years since menopause was 7.5 ± 5.6 (0. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. The mean number of deliveries were 2.9 ± 1.4 (0-9).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown that surgery to address stress urinary incontinence (SUI) has a positive impact on sexual function, particularly with resolution of coital incontinence. 7,8 In a systematic review of 18 studies addressing sexual function post-SUI surgery, 32% of patients reported an improvement, 55% reported no change and a small but still substantial 13% of patients reported worsening of sexual function. Improvements in sexual health following treatment for SUI are due to a reduction in coital incontinence; it has not been shown that surgery has any impact on other aspects of sexual function such as desire, arousal or orgasm.…”
Section: Urinary Incontinence and Sexual Healthmentioning
confidence: 99%